The impact of mobile banking adoption on financial performance: a case of Central Africa Building Society (CABS). - Chiinze, Hilda Tinotenda (Midlands State University, 2017)
The purpose of the research was to investigate the impact of mobile banking on financial performance, using CABS a case. The research was mainly aimed at assessing the relationship between mobile banking and financial performance, identifying the risks associated with mobile banking, establishing the critical internal and external factors for successful mobile banking, identifying performance benefits and ways in which mobile banking has contributed to the overall performance of CABS. The study used a descriptive research design and data was presented using tables, graphs and charts. A sample of 28 participants was drawn out of a target population of 40 participants from finance, internal audit and electronic banking departments at CABS. It was found out that mobile banking, adoption affects financial performance positively and that the risks that affect mobile banking the most are fraud and money laundering. The study recommended for CABS to increase their investment in mobile banking. CABS should make a more active effort to educate its clients about the benefits of mobile banking and hence the stand to benefit much more from the adoption of mobile banking.